2017
DOI: 10.1371/journal.pone.0173904
|View full text |Cite
|
Sign up to set email alerts
|

Use of the 9-item Shared Decision Making Questionnaire (SDM-Q-9 and SDM-Q-Doc) in intervention studies—A systematic review

Abstract: BackgroundThe Shared Decision Making Questionnaire (SDM-Q-9 and SDM-Q-Doc) is a 9-item measure of the decisional process in medical encounters from both patients’ and physicians’ perspectives. It has good acceptance, feasibility, and reliability. This systematic review aimed to 1) evaluate the use of the SDM-Q-9 and SDM-Q-Doc in intervention studies on shared decision making (SDM) in clinical settings, 2) describe how the SDM-Q-9 and SDM-Q-Doc performed regarding sensitivity to change, and 3) assess the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 63 publications
6
94
1
1
Order By: Relevance
“…Other subjective metrics, such as the SDM‐Q‐9 and SDM‐Q‐Doc questionnaires, showed slightly higher levels of SDM in surgery than in other medical specialties. For example, Doherr and co‐workers reported mean total SDM‐Q‐9 and SDM‐Q‐Doc scores ranging from 42 to 75 per cent. These high subjective SDM levels in surgical studies may also be caused by a misinterpretation of the informed consent procedure for SDM.…”
Section: Discussionmentioning
confidence: 99%
“…Other subjective metrics, such as the SDM‐Q‐9 and SDM‐Q‐Doc questionnaires, showed slightly higher levels of SDM in surgery than in other medical specialties. For example, Doherr and co‐workers reported mean total SDM‐Q‐9 and SDM‐Q‐Doc scores ranging from 42 to 75 per cent. These high subjective SDM levels in surgical studies may also be caused by a misinterpretation of the informed consent procedure for SDM.…”
Section: Discussionmentioning
confidence: 99%
“…This has made comparisons and examination of the effects of collaborative provider-patient interventions difficult. 22,23 In two randomized controlled trials, nurse-led information provision and counseling were shown to have the potential to increase informed choices. 24,25 However, a systematic review of randomized controlled trials and quasi-randomized trials evaluating the effectiveness of information-sharing approaches between providers and patients with MS found mixed results.…”
Section: Assessment Of Adherence and Sdmmentioning
confidence: 99%
“…28 The SDM-Q-9, in which patients evaluate the quality of nine aspects of the decision-making process, 28 is the most frequently used of the three scales. 22 However, a systematic review of studies evaluating the SDM-Q-9 revealed poor quality of evidence, suggesting that its value as an assessment tool may be limited. 22…”
Section: Assessment Of Adherence and Sdmmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate implementation, ED providers and staff will be asked to complete baseline, 3-, 6-, and 12-month CFIR surveys to evaluate the implementation process, with attention to acceptability, implementation barriers, and facilitators. A validated 3item pediatric CollaboRate survey and 9-item questionnaire SDM-Q-DOC will evaluate the decisional process in medical encounters from the physicians' perspectives at the specified time points [42][43][44]. Patient satisfaction with Coach McLungs SM will be assessed using the oneitem Net Promoter Score question [45][46][47].…”
Section: Methodsmentioning
confidence: 99%